Entre trajetórias institucionais e companhias de dança: uma avaliação da política cultural dos editais de dança da Prefeitura Municipal de Fortaleza (2005-2012) - Silva, Júlia Cândida Soares Menezes (2015)
The objective of this study is to evaluate the edicts policy of encouragement to promote the area of dance, edicts developed by the Fortaleza City Hall in 2006, along with the national policy of the Lula government culture. With the creation of edicts policy, funds were granted through public selection. First, we use the text of the edicts policy and the artistic trajectory of Cia Dita and the Hundred Group, which won the promotion prize of the First Municipal Edict. So we try to understand if the notices have contributed to promoting changes in dance companies that won awards. For this we use a policy assessment model the hermeneutic paradigm to understand, emphasizing links between the context and the history of policy, through three evaluative dimensions: organizational, esthetic and financial. The results of this evaluation show that the promotion edicts policy did not contemplate and not changed, fully, the area of dance in Fortaleza. What really happened were specific changes in dance companies that won the encouragement prize.